2021
DOI: 10.1186/s41938-021-00413-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal activity of endophytic bacteria isolated from date palm (Phoenix doctylifera L.) against fungal pathogens causing leaf spot of date palm

Abstract: Background Date palm ((Phoenix doctylifera L.) suffers from several fungal diseases. The endophytic microorganisms present in higher plants generally offer protection to their host plants against invading phytopathogenic fungi and bacteria. In the present study, endophytic bacteria associated with date palm leaves were isolated and their in vitro antagonistic potential against fungal pathogens causing leaf spots in date palm was demonstrated. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…The current study shows that the inoculation of plants with endophytic bacteria with phosphate solubilization (PSB) and IAA production resulted in greater plant growth than un-inoculated plants. These results are consistent with some previous reports, in which the use of PSB enhanced growth, yield, and quality in many crops including walnut, apple, maize, rice, mustard, oil palm, aubergine and chili, soybean, wheat, sugar beet, sugarcane, chickpea, peanut and legumes, and potatoes [36,41]. It is proposed that the antagonistic bacteria in this study produced extracellular metabolites (such as GA) that resulted in the release of soluble phosphate and subsequently up-took by the plant [42].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study shows that the inoculation of plants with endophytic bacteria with phosphate solubilization (PSB) and IAA production resulted in greater plant growth than un-inoculated plants. These results are consistent with some previous reports, in which the use of PSB enhanced growth, yield, and quality in many crops including walnut, apple, maize, rice, mustard, oil palm, aubergine and chili, soybean, wheat, sugar beet, sugarcane, chickpea, peanut and legumes, and potatoes [36,41]. It is proposed that the antagonistic bacteria in this study produced extracellular metabolites (such as GA) that resulted in the release of soluble phosphate and subsequently up-took by the plant [42].…”
Section: Discussionsupporting
confidence: 93%
“…These compounds caused leakage of cellular electrolytes from the mycelium of A. alternata resulting in the shrinkage of hyphae. The leakage of electrolytes from fungal membranes has previously been reported as an indicator of cell membrane damage [35,36]. The results of the present study suggest the production of antifungal compounds as one of the possible mechanisms of action of these endophytic bacterial strains on the tested fungal pathogens.…”
Section: Discussionsupporting
confidence: 64%
“…Some studies consider bacterial endophytes as potential biocontrol agents for various hazardous fungi [ 6 , 7 ]. Selim et al [ 17 ] and Riera et al [ 49 ] revealed that Streptomyces , Pseudomonas , Bacillus , and Agrobacterium have long been the most important bacteria genera for the production of active antimicrobial substances.…”
Section: Discussionmentioning
confidence: 99%
“…The biological methods of controlling diseases that affect plants is an eco-friendly alternative, especially applicable when there is pesticide resistance and the need for environmental protection toward sustainable agricultural methods [ 4 , 5 ]. Microbial antagonists have unique properties that inhibit fungal infection growth through direct and indirect processes [ 6 , 7 ]. The direct impact is mainly owing to the biocontrol agent’s antagonistic behavior against the pathogen due to competition, parasitism, antibiosis, and the production of extracellular digestive enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation